Concurrence of NMOSD and ALS in a patient with hexanucleotide repeat expansions of C9orf72. Issue 5 (3rd July 2019) - Falzone, Yuri Matteo; Radaelli, Marta; Agosta, Federica; Domi, Teuta; Guerrieri, Simone; Spinelli, Edoardo Gioele; Pozzi, Laura; Carrera, Paola; Ferrari, Maurizio; Comi, Giancarlo; Filippi, Massimo; Quattrini, Angelo; et al.
Abstract: We describe a patient, previously known for NMOSD, who presented a rapidly progressive worsening of muscle strength, respiratory, and bulbar functions. ALS associated with cognitive impairment was diagnosed, while genetic analysis revealed a hexanucleotide repeat expansion in the C9orf72 gene. To the best of our knowledge, this is the first reported C9orf72-ALS patient with concurrent NMOSD. In consideration of the low prevalence of these two diseases, a by-chance co-occurrence is unlikely. Although the discovery of a disease-specific serum AQP4-IgG antibody has led to a broadening of the NMOSD, a progressive neurological deterioration, as shown by our patient, should be considered as a "red flag", leading to alternative diagnostic hypotheses. Our report supports the hypothesis that in C9orf72-ALS neuroinflammation may contribute to disease penetrance or to determine an aggressive clinical phenotype. Further investigations are needed in order to establish possible shared neuroinflammatory patterns between ALS, NMOSD, and other neuroinflammatory disorders.